ANTARA KECEMASAN DAN MINIMALISME: MEMPREDIKSI PERILAKU KONSUMTIF PADA WANITA SHOPAHOLIC DEWASA AWAL - Rif'ati, Almaas; Malahati, Fildzah (SINERGI : Jurnal Riset Ilmiah, 2025)
This research is motivated by the problems that occur in early adult women who experience social pressure due to the change from adolescence to adulthood. Where social life requires individuals to have independence both economically and financially which is based on changes in a new, more modern lifestyle. The inability of individuals to meet these social demands often causes anxiety, and stress which triggers consumptive behavior. Uncontrollable consumptive behavior will be attached to the individual and is known as shopaholic. This study aims to examine the impact of anxiety and minimalist living attitudes on consumptive behavior in early adult shopaholic women. The quantitative method was chosen to determine the relationship between the three variables. The results of the study showed that there was a very significant relationship between anxiety and minimalist living attitude to consumptive behavior in early adult shopaholic women. This research contributes new findings to science in the field of psychology and social